Police leadership 2.0.: A comprehensive systematic review of the literature - Moura, R. C. de.; Borges, A.; Morgado, S.; Ramalho, N. (Policing: A journal of policy and practice, 2023)
Police are required to operate in complex social, political, and organizational environments. Nowadays, challenging times highlight the role that police leaders play in ensuring that the organization is effective in dealing with such environments. The purpose of this paper is to expand the systematic review of literature of Pearson-Goff and Herrington (2014, ‘Police Leadership: A Systematic Review of the Literature.’ Policing: A Journal of Policy and Practice 8(1): 14–26) by: (1) including studies after the date considered by the authors; (2) following the PRISMA-P approach to systematic reviews; and (3) include European studies. Based on 7,041 records, which ended up in 101 eligible empirical pieces, evidence supports previous findings about what are the characteristics of police leaders as well as the actions expected by them. This comprehensive systematic review also identifies additional characteristics and actions that are important nowadays in police leadership. Overall, the current study encourages future studies on the thematic, and contributes to practitioners aiming to develop continuous improvement strategies inside the police.